Mama Miti : Wangari Maathai and the trees of Kenya - Napoli, Donna Jo, 1948- (Simon & Schuster Books for Young Readers, 2010)
The story of Wangari Maathai, who in 1977 founded the Green Belt Movement, an African grassroots organization, and in 2004 was the first African woman to be awarded the Nobel Peace Prize.